Back to Thin-Core Massively Parallel Processors. - Marowka, Ami (Computer (00189162), 2011)
Examination of the innovations of the past three decades that brought chips to the point at which many-core processors are possible reveals that there are multiple roads ahead, and each is full of challenges.